Frijol (Phaseolus vulgaris L.) - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1983)
A methodology to describe quality and quantity characteristics of bean var. is presented. A complete list of data that should be taken is included and each item is explained. Data are classified according to the growth stage in which they should be taken: seedling, flowering, pod fill, physiological maturity, and at harvest. Other data include the reaction to diseases and pests, way of consumption, and var. that most resemble the described characteristics. Model formats for data recording are included as well as guidelines and requirements for bean seed production. (CIAT)